I fiori blu ed il Teatro Possibile: due esperienze teatrali che raccontano la costruzione di uno spazio sicuro - Maura Perrone1, Giovanna Maciariello2, Adriano De Blasi3, Anna Di Leva4 (Marp Edizioni, 2023)
The needs for protection and security are the starting point from which every human being develops his relational and affective evolutionary model. his article highlights how the safe space, in which the human being evolves, is given by the interaction of the individual dimension in which the person perceives himself protected and free to act in his reference context, and a collective dimension, understood as an ecological niche that conveys a sense of security to human beings in order to develop their individuality and create social relationships. Furthermore, the emphasis is placed on the importance of the safe space as a facilitator of learning and channeler of educational activities, in particular for that segment of the population affected by psychic and social difficulties. The authors identify in theatrical practice the possibility of creating a safe space in which the creation, sharing and expression of one's needs and experiences is possible.